TINJAUAN YURIDIS NORMATIF TERHADAP PERAN DAN FUNGSI ADVOKAT DALAM PENYELESAIAN PERKARA PERDATA - Nur Hasan (Jurnal Ilmiah Universitas Batanghari Jambi, 2017)
An advocate is a person who berfropesi to give legal services both inside and outside the Court meet the requirements based on the provisions of the Act. The role of an advocate in providing legal services in civil matters is that the Advocate as a recipient of the power or the plaintiff or defendant from representing in the beracara in front of the Court to explain and straighten out the facts and evidence put forward by its clients, so that they can assist and facilitate the judge in taking a decision.In carrying out its functions and perananya of the civil code in the case of the powerlaw is obliged to execute the code etiknya as legal advisor. The job of an advocate or a legal advisor is as trust. Thus the relationship between legal counsel with clientsmust be prefixed with a trust relationship. So the relationship between legal counselwith clients can run in accordance with the code of ethics that has been determinedfor legal counsel. Advocates in carrying out tasks of work prohibited to differentiatethe treatment of Clients on the basis of gender, religion, race, descent, political, or social and cultural background.Keyword: advocate, civil litigation